The role of Smart Education (SE) in supporting Digital Eco-Literacy (DEL) Aminah Zuhriyah - Aminah Zuhriyah (Faculty of Geography, Universitas Gadjah Mada, 2023)
The rapid development of computer technology today has implications for high quality educational services and resources. Meanwhile, this era of Smart Education (SE) has given a new picture that the openness and sharing of global knowledge become a top priority for the advancement of education, especially in Digital Eco-Literacy (DEL) learning. The study aims to understand in depth the role of Smart Education (SE) in supporting the development of Digital Eco-Literacy (DEL). The research method used is a qualitative technique with a review paper approach. The findings show that SE will be the key to effectively and efficiently developing DEL Learning. A positive impact on improving student achievement and the ability to understand various environmental problems with a more dynamic and innovative perspective should be considered.